Patient-centered care interventions to reduce the inappropriate prescription and use of benzodiazepines and z-drugs: a systematic review - Aliaksandra Mokhar (PeerJ, 2018)
Background Benzodiazepines (BZDs) and z-drugs are effective drugs, but they are prescribed excessively worldwide. International guidelines recommend a maximum treatment duration of 4 weeks. Although these drugs are effective in the short-term, long-term BZD therapy is associated with considerable adverse effects, the development of tolerance and, finally, addiction. However, there are different interventions in terms of patient-centered care that aim to reduce the use of BZDs and z-drugs as well as assist health care professionals (HCPs) in preventing the inappropriate prescription of BZDs. Aim The aim of this systematic review was to identify interventions that promote patient-centered treatments for inappropriate BZD and z-drug use and to analyze their effectiveness in reducing the inappropriate use of these drugs. Methods To identify relevant studies, the PubMed, EMBASE, PsycINFO, Psyndex, and Cochrane Library databases were searched. Studies with controlled designs focusing on adult patients were included. Trials with chronically or mentally ill patients were excluded if long-term BZD and z-drug use was indicated. Study extraction was performed based on the Cochrane Form for study extraction. To assess the quality of the studies, we used a tool based on the Cochrane Collaboration’s tool for assessing the risk of bias in randomized trials. Results We identified 7,068 studies and selected 20 for systematic review. Nine interventions focused on patients, nine on HCPs, and two on both patients and HCPs. Intervention types ranged from simple to multifaceted. Patient-centered interventions that provided patient information effectively increased the appropriate use of BZDs. The educational approaches for HCPs that aimed to achieve appropriate prescription reported inconsistent results. The methods that combined informing patients and HCPs led to a significant reduction in BZD use. Conclusions This is the first review of studies focused on patient-centered approaches to reducing the inappropriate prescription and use of BZDs and z-drugs. The patient-centered dimension of patient information was responsible for a decrease in BZD and z-drug consumption. Further, in some studies, the patient-centered dimensions responsible for reducing the prescription and use of BZDs and z-drugs were the clinician’s essential characteristics and clinician-patient communication.